Hyperglycemia and blood pressure treatment goal: a cross sectional survey of 18350 patients with type 2 diabetes in 77 tertiary hospitals in China. - Linong Ji (Public Library of Science (PLoS), 2014)
Objective To investigate the association of hyperglycemia with blood pressure control goal in the patients with type 2 diabetes (T2D) cared by tertiary hospitals in China. Study design and methods A cross sectional survey of 29442 patients was conducted in 77 tertiary hospitals in 4 major cities in China in 2011 and 18350 of them without known hypertension were used in the analysis. Univariable and multivariable logistic regression analysis stratified on cities and hospitals was performed to obtain odds ratio of factors of interest for achievement of the blood pressure treatment goal, i.e., 140/80 mmHg as recommended by American Diabetes Association (ADA). Sensitivity analysis was performed after re-inclusion of 11902 patients with diagnosed hypertension. Findings from were further replicated in patients with T2D recruited using the same protocol from tertiary hospitals located in other central cities in China. Results The mean age was 58.2 (SD: 11.3) years and 53.3% were male, with a median of 4 years of disease duration. A total of 12129 patients (58.2%) did not achieve the ADA recommended goal for BP control. After adjusting for covariables, hyperglycemia was associated with failure to achieve the BP goal (OR of HbA1c at 6.5%-6.9% vs. <6.0%: 1.22, 95%CI: 1.08 to 1.39; OR of 7.0%-7.0% vs. <6.0%: 1.37, 1.21 to 1.54 and OR of ≥ 8.0% vs. <6.0%: 1.22, 95%CI: 1.08 to 1.38). The sensitivity analysis and the replication analysis showed similar results. Conclusions Hyperglycemia defined as HbA1c ≥ 6.5% increased the risk of failure to achieve the BP goal in T2D patients.